Preparation method and application of anion intercalation r-Ru-coated NiFe-LDH catalyst

By forming anionic intercalation on iron foam, the problems of catalyst stability and chlorine resistance in electrolytic seawater are solved, and efficient electrocatalytic performance and low-cost production are achieved, suitable for large currents Electrolytic seawater application at density.

CN119265616APending Publication Date: 2025-01-07JIANGXI KEXING ENERGY STORAGE TECHNOLOGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411343059.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing electrolytic seawater catalysts have poor stability and catalytic activity under the erosion of chloride ions in seawater, especially the chlorine resistance and stability of non-precious metal-based catalysts such as NiFe-LDH are difficult to improve, and traditional methods require additional iron salts to increase cost and complexity.

Method used

By performing anion intercalation treatment on the foam iron, an r-Ru@NiFe-LDH catalyst is formed, and hydrothermal reaction and ruthenium doping technology are used to optimize the content and structure of nickel and iron, and the stability and chlorine resistance of the catalyst are improved. And avoid additional iron salt by in-situ construction.

Benefits of technology

It improves the activity and stability of the catalyst, enhances the resistance to chloride ions, reduces production costs, maintains efficient electrocatalytic performance under high current density, and significantly improves the crystallinity and purity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265616A_ABST
    Figure CN119265616A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of electrolyzed water catalysts, and particularly relates to a preparation method and application of an anion intercalation r-Ru-NiFe-LDH catalyst. The foam iron is subjected to washing pretreatment and freeze drying; the preparation method comprises the following steps: putting foam iron into an alkaline aqueous solution of nickel salt, and carrying out hydrothermal reaction to obtain an anion intercalated NiFe-LDH precursor growing on the foam iron; and putting the anion intercalated NiFe-LDH precursor into a ruthenium chloride solution, carrying out hydrothermal reaction again, taking out, drying, and carrying out reduction treatment to obtain the anion intercalated ruthenium-loaded NiFe-LDH catalyst growing on the foam iron. The invention provides a new idea for research and development of a seawater electrolysis bifunctional catalyst with high activity and stability under high current density, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of water electrolysis catalysts, and specifically relates to a preparation method and application of an anion intercalation r-Ru@NiFe-LDH catalyst. Background Art

[0002] With the development of social economy, resource depletion, air pollution and water pollution are becoming more and more serious. Among many energy sources, hydrogen energy is a very promising "secondary energy" and is also regarded as an ideal "green energy". Water electrolysis technology has become one of the important production methods of green hydrogen due to its advantages such as environmental friendliness and pure hydrogen production.

[0003] Compared with seawater resources, the freshwater resources available to people are quite limited. Therefore, it is of great significance to use seawater, which accounts for the largest proportion of the world's water resources, as an electrolyte in water electrolysis technology. However, due to the presence of a large number of chloride ions in seawater, the catalyst will be seriously corroded, resulting in catalyst deactivation and decreased stability. Therefore, the preparation of electrolytic seawater catalysts with excellent chlorine resistance and catalytic activity has attracted special attention.

[0004] At present, catalysts for electrolysis of seawater can be roughly divided into precious metal-based catalysts (such as Pt, Ir, etc.) and non-precious metal-based catalysts (such as transition metals, etc.). Precious metal-based catalysts have high activity, but high cost. Non-precious metal catalysts have a significant price advantage, but poor activity. Among many non-precious metal materials, NiFe-LDH (NiFe double hydroxide) has attracted much attention from the academic community because of its high catalytic activity for OER. However, in the seawater electrolyte environment, the presence of chloride ions will corrode it, reducing its stability and catalytic activity. Inserting different anions into the interlayer of NiFe-LDH and using the charge repulsion effect to prevent chloride ions in seawater from diffusing to the surface of the catalyst is one of the effective ways to solve the corrosion of the catalyst. In addition, the interlayer deformation of NiFe-LDH can be regulated to cause the oxygen atoms in the LDH main layer to detach to form oxygen vacancies, further leading to electronic effects and improving catalytic activity.

[0005] Patent CN117987846A discloses a preparation method and application of NiM-LDH-N / FF, wherein the foamed iron is ultrasonically cleaned and then vacuum dried; the treated foamed iron is placed in a reactor containing a nickel salt, another transition metal salt, hexamethylenetetramine and methanol for a solvothermal reaction to generate a layered double metal hydroxide-foamed iron complex; the layered double metal hydroxide-foamed iron complex is placed in a reactor containing a nickel salt, ammonium chloride and methanol for a secondary solvothermal reaction to generate NiM-LDH-N / FF. Although this method also loads LDH on the foamed iron, it requires the additional addition of iron salts and is not doped and modified, so the electrocatalytic activity still needs to be improved, and it is not mentioned whether the chlorine resistance can be solved.

[0006] Therefore, it is necessary to provide an improved anion intercalation r-Ru@NiFe-LDH / IF to solve the above problems. Summary of the invention

[0007] The object of the present invention is to provide a preparation method of an anion intercalated r-Ru@NiFe-LDH / IF catalyst and its application, so as to improve the activity, chlorine resistance and stability of the catalyst.

[0008] To achieve the above object, the present invention provides a method for preparing an anion intercalated r-Ru@NiFe-LDH / IF catalyst, comprising the following steps:

[0009] S1, placing the cleaned foamed iron into an alkaline aqueous solution of nickel salt for hydrothermal reaction to obtain a NiFe-LDH precursor with an anion intercalation layer grown on the foamed iron;

[0010] S2. The anion-intercalated NiFe-LDH precursor is placed in a ruthenium chloride solution for a hydrothermal reaction again, and then taken out and dried, and the ruthenium oxide is reduced to obtain an anion-intercalated ruthenium-loaded NiFe-LDH catalyst grown on the foamed iron.

[0011] Further, in step S1, the nickel salt is a mixture of nickel chloride hexahydrate and terephthalic acid, one or more of nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel acetylacetonate;

[0012] And / or, the alkalinity of the alkaline aqueous solution is regulated by one or more of urea, hexamethylenetetramine, ammonia water, sodium hydroxide, and potassium hydroxide, preferably urea.

[0013] Further, the nickel salt and urea are used in a ratio of 1-3 mmol:5 mmol; the terephthalic acid and nickel chloride hexahydrate are used in a ratio of 0.1-0.3 mmol:2 mmol, preferably 0.2 mmol:2 mmol. Preferably, in the alkaline aqueous solution of the nickel salt, the nickel salt, urea and deionized water are used in a ratio of 1-3 mmol:5 mmol:20 mL; further preferably, the nickel salt, urea and deionized water are used in a ratio of 2 mmol:5 mmol:20 mL.

[0014] Furthermore, in steps S1 and S2, the temperature of the hydrothermal reaction is 100-150°C, and the reaction time is 10-15 hours. More preferably, the temperature of the hydrothermal reaction is 120°C, and the reaction time is 12 hours.

[0015] Furthermore, in step S2, the concentration of the ruthenium chloride solution is 10-14 mmol / L, preferably 12 mmol / L, and the ratio of the nickel salt to the ruthenium chloride is 1-3 mmol: 0.2-0.28 mmol. In the system of the present invention, the doping amount of ruthenium also has a greater influence on the performance of the catalyst. By optimizing its dosage, a catalyst with better catalytic performance can be obtained. Moreover, the ruthenium chloride salt solution helps the secondary corrosion of the foamed iron to produce iron ions, thereby promoting the improvement of the LDH structure.

[0016] Furthermore, in step S2, the reduction treatment is performed by thermal reduction in a mixed atmosphere of Ar and H2;

[0017] The volume ratio of Ar to H2 is 1:(8-12), and the flow rate is 80-120 mL / min; the thermal reduction is performed by heat treatment from room temperature at a heating rate of 8-10°C / min to 90-110°C for 1-3 hours.

[0018] Preferably, the volume ratio of Ar to H2 is 1:10, and the flow rate is 100 mL / min; the thermal reduction is a heat treatment from room temperature to 100°C at a heating rate of 10°C / min for 2 hours.

[0019] Furthermore, in step S1, the foamed iron is ultrasonically washed with anhydrous ethanol, 2-4 mol / L hydrochloric acid (preferably 3 mol / L), and deionized water in sequence for 5-15 min, preferably 10 min.

[0020] In a second aspect, the present invention provides an anion intercalated r-Ru@NiFe-LDH / IF catalyst obtained by any of the preparation methods described above.

[0021] In a third aspect, the present invention further provides an application of an anion intercalated r-Ru@NiFe-LDH / IF catalyst, wherein the anion intercalated r-Ru@NiFe-LDH / IF catalyst is used for electrolysis of water to produce hydrogen or oxygen.

[0022] Furthermore, the water is seawater or simulated seawater, and the simulated seawater contains 1 mol / L KOH and 0.5 mol / L NaCl.

[0023] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0024] 1. The present invention uses low-cost foamed iron as a substrate material. On the one hand, due to its own 3D rigid mesh structure, it can provide a larger surface area to carry more active sites, thereby increasing the stability of the catalyst; on the other hand, it can effectively improve the conductivity of the catalyst and accelerate the transfer of electrons to the active sites; in addition, it can also be used as a direct source of iron ions in this catalyst, without the need to add iron salts to the system, to promote the in-situ construction of double metal hydroxides, and to be able to well regulate the content of nickel and iron in the double metal LDH, the preparation method is more convenient and concise, the prepared catalyst has a high degree of crystallization, an increase in active sites, and improved electrocatalytic performance. Through the secondary hydrothermal reaction, both the doping of ruthenium and the further improvement of the NiFe-LDH structure can be achieved, so the catalytic performance is further improved.

[0025] 2. The present invention uses a two-step hydrothermal method to obtain a catalyst with higher purity and better crystallinity. The in-situ construction method on the foamed iron avoids the problem of traditional powder catalysts peeling off from the electrode as the current density increases; on the other hand, it can also effectively solve the problem of the active sites of the catalyst being covered by the binder, thereby improving the catalytic activity.

[0026] 3. The present invention uses the charge repulsion effect to prevent chloride ions in seawater from diffusing to the surface of the catalyst by inserting anions into the interlayer of r-Ru@NiFe-LDH / IF, thereby solving the corrosion of the electrode surface by chloride ions at a low cost. In addition, the interlayer deformation of NiFe-LDH can be regulated to cause the oxygen atoms in the LDH main layer to detach and form oxygen vacancies, thereby regulating the electrocatalytic performance, so that a larger current density can be driven at a lower potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The scanning electron microscope (SEM) images and elemental mapping (EDS) images of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5;

[0028] Figure 2X-ray diffraction (XRD) spectra of NiFe-LDH with different anion intercalation in Examples 1-5;

[0029] Figure 3 X-ray diffraction (XRD) spectra of Ru@NiFe-LDH with different anion intercalation in Examples 1-5;

[0030] Figure 4 X-ray diffraction (XRD) spectra of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5;

[0031] Figure 5 The X-ray photoelectron spectroscopy (XPS) spectra of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5;

[0032] Figure 6 The Raman scattering spectra (Raman) of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5;

[0033] Figure 7 The linear polarization curves (LSV) of HER of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5 in nitrogen-saturated 1M KOH+0.5M NaCl electrolyte;

[0034] Figure 8 Linear polarization curves (LSV) of OER of r-Ru@NiFe-LDH with different anion intercalation in Examples 1-5 in oxygen-saturated 1M KOH+0.5M NaCl electrolyte;

[0035] Fig. 9 SO4 of Example 1 2- -Linear polarization curve (LSV) of the complete hydrolysis of r-Ru@NiFe-LDH in 1M KOH+0.5M NaCl electrolyte;

[0036] Fig.10 SO4 of Example 1 2- Chronopotentiometry curves of HER and OER of -r-Ru@NiFe-LDH in 1M KOH+0.5M NaCl electrolyte for 160 h. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0038] The invention provides a preparation method of an anion intercalation r-Ru@NiFe-LDH / IF catalyst, comprising: washing and pre-treating foamed iron, and freeze-drying; placing the treated foamed iron in a reactor containing nickel salts of different anions, urea and deionized water for hydrothermal reaction to obtain NiFe-LDH / IF precursors with different anion intercalations; placing the precursor in a reactor containing anhydrous ruthenium chloride solution for hydrothermal reaction again to obtain Ru@NiFe-LDH / IF catalysts with different anion intercalations; and finally placing the materials in a tubular furnace for thermal reduction under an Ar / H2 atmosphere to obtain r-Ru@NiFe-LDH / IF catalysts with different anion intercalations.

[0039] The present invention uses foamed iron as a catalyst substrate, which, when in hot alkaline solution, comes into contact with water or oxygen dissolved in water, will undergo an oxygen absorption corrosion reaction, which eventually causes the surface of the iron to gradually dissolve and release iron ions. This method not only does not require the addition of additional iron salts, but also reduces the production cost of the catalyst. It also improves the catalytic performance and stability of the catalyst by regulating oxygen vacancies. Among them, the prepared sulfate intercalated r-Ru@NiFe-LDH / IF catalyst, when used as an anode material for electrolysis of simulated seawater, can drive 500mA cm with only 350mV overpotential. -2 When used as a cathode material for electrolysis of simulated seawater, it only needs an overpotential of 211 mV to drive 500 mA cm -2 This method provides a new idea for the development of bifunctional catalysts for seawater electrolysis with high activity and stability at high current density, and has broad prospects for industrial application.

[0040] Example 1

[0041] (1) Foamed iron (IF) was cut into a size of 2 cm × 2 cm, and ultrasonically washed with anhydrous ethanol, 3 mol / L hydrochloric acid, and deionized water for 10 min in sequence, and then dried in a freeze dryer for 10 h to obtain clean foamed iron after pretreatment.

[0042] (2) Add 0.5257 g of nickel sulfate hexahydrate, 300 mg of urea and 20 mL of deionized water to the reactor and stir for 10 min. After the solid is completely dissolved, put the pretreated foamed iron into the reactor for a hydrothermal reaction at 120°C for 12 h. After the reaction time is over and the temperature reaches room temperature, open the reactor, take out the sample, wash it three times with deionized water and anhydrous ethanol respectively, and finally put it into a freeze dryer for 10 h to obtain a nickel-iron double metal hydroxide (SO4 2- -NiFe-LDH / IF).

[0043] (3) Take 20 mL of 12 mmol / L ruthenium chloride solution in a reactor, and then add SO4 2- -NiFe-LDH / IF was placed in it for a hydrothermal reaction at 120°C for 12 hours. After the reaction time was over and the temperature reached room temperature, the reactor was opened and the sample was taken out and washed three times with deionized water and anhydrous ethanol respectively, and finally placed in a freeze dryer for 10 hours to obtain ruthenium-doped sulfate ion intercalated nickel-iron double hydroxide (SO4 2- -Ru@NiFe-LDH / IF).

[0044] (4) SO4 2- -Ru@NiFe-LDH / IF was placed in a porcelain boat and placed in a quartz tube, and heat treated for 2 h at a heating rate of 10°C / min from room temperature to 100°C in an Ar / H2 mixed atmosphere with a H2 volume fraction of 10%. After the reaction was completed and the temperature reached room temperature, the sample was taken out of the quartz tube to obtain a reduced ruthenium-doped sulfate ion intercalated nickel-iron double hydroxide (SO4 2- -r-Ru@NiFe-LDH / IF).

[0045] It was found during the experiment of the present invention that when iron salt was added in the hydrothermal reaction, the material loaded on the foamed iron was easily agglomerated and hardened after drying. The reason may be that after the iron salt was added, the iron content in the system was too much, and the nickel-iron ratio was excessively unbalanced. Therefore, the present invention only uses the iron ions generated by the corrosion of the foamed iron as the iron source, which can simplify the process, regulate the product morphology, and improve the catalytic performance.

[0046] Example 2

[0047] This embodiment provides a catalyst, which is different from that of embodiment 1 in that nickel sulfate hexahydrate is replaced with 0.5816 g of nickel nitrate hexahydrate to obtain a nickel-iron double metal hydroxide (NO3 - -r-Ru@NiFe-LDH / IF).

[0048] Example 3

[0049] This embodiment provides a catalyst, which is different from that of embodiment 1 in that nickel sulfate hexahydrate is replaced with 0.47538 g of nickel chloride hexahydrate to obtain a reduced ruthenium-doped chloride-intercalated nickel-iron double hydroxide (Cl - -r-Ru@NiFe-LDH / IF).

[0050] Example 4

[0051] This embodiment provides a catalyst, which is different from Example 1 in that nickel sulfate hexahydrate is replaced with 0.51382 g of nickel acetylacetonate to obtain a reduced ruthenium-doped acetylacetonate ion-intercalated nickel-iron double hydroxide (acac-r-Ru@NiFe-LDH / IF).

[0052] Example 5

[0053] This embodiment provides a catalyst, which is different from Example 1 in that nickel sulfate is replaced with a mixed salt of 0.47538 g of nickel chloride hexahydrate and 40 mg of terephthalic acid to obtain a reduced ruthenium-doped terephthalate ion intercalated nickel-iron double hydroxide (TA-r-Ru@NiFe-LDH / IF).

[0054] The scanning electron microscope images of the catalysts prepared in Examples 1-5 and the corresponding element mapping images of different elements are shown in FIG. Figure 1 As shown, it can be observed that the nanoflower-like structure of r-Ru@NiFe-LDH with various anion intercalations is grown on the foam iron substrate, and the corresponding elements are evenly distributed on the sample surface. The in situ growth of uniform and abundant nanosheets is beneficial to increasing the specific surface area of ​​the catalyst, while the abundant foam iron 3D structure is beneficial to the generated gas leaving the electrode and promoting mass transfer.

[0055] The X-ray diffraction patterns of the materials prepared in Examples 1-5 are as follows: Figure 2-4 As shown, Figure 2 XRD patterns of NiFe-LDH / IF with different anion intercalation. Figure 2 It can be observed that the peaks of the prepared series of materials are consistent with the standard PDF card of NiFe-LDH. With the increase of the radius of the intercalated anion, the half-peak widths of the peaks corresponding to 11.5°, 34.5°, 39.0°, 60.3° and 61.2° also increase successively. When the interlayer anion is too large (such as TA-NiFe-LDH / IF), the above peaks almost disappear, indicating that the layered structure is almost destroyed. Therefore, the difference in the radius of the interlayer anion can change the interlayer structure of NiFe-LDH. Figure 3 The XRD patterns of Ru@NiFe-LDH / IF with different anion intercalation are shown in Figure 2. Figure 3 It can be observed that the peaks of the prepared series of materials still have the characteristic peaks of NiFe-LDH, but the positions of the peaks have shifted, proving that Ru has been doped into NiFe-LDH. Figure 4 The XRD patterns of r-Ru@NiFe-LDH / IF with different anion intercalation are shown in Figure 2. Figure 4 It can be observed that the material reduced by H2 still retains the typical structure of NiFe-LDH.

[0056] The X-ray photoelectron spectra of r-Ru@NiFe-LDH / IF with different anion intercalation prepared in Examples 1-5 are shown in Figure 2. Figure 5 As shown in the figure, it can be observed that Ni, Fe, O, Ru, C and Cl elements exist in each sample. In particular, in SO4 2- -r-Ru@NiFe-LDH / IF contains S element, in NO3 - -r-Ru@NiFe-LDH / IF contains N element. With the insertion of anions, the intensity of O1s peak near 530eV changes, indicating that interlayer deformation causes oxygen atoms in the LDH main layer to detach and form abundant oxygen vacancies. These results also confirm the results of XRD, indicating the successful synthesis of r-Ru@NiFe-LDH / IF with different anion intercalation.

[0057] The Raman spectra of r-Ru@NiFe-LDH / IF with different anion intercalation prepared in Examples 1-5 are as follows: Figure 6 As shown in the figure, it can be observed that each sample has the structure of NiFe-LDH. 2- -r-Ru@NiFe-LDH / IF, at 1000cm -1 The peak of SO bond can be retrieved nearby, which is attributed to SO4 2- The existence of NO3 - -r-Ru@NiFe-LDH / IF, at 1050cm -1 The peak of NO bond can be retrieved nearby, which is attributed to NO3 - For TA-r-Ru@NiFe-LDH / IF, at 1612cm -1 The peak of C=C bond can be retrieved nearby, which is attributed to C6H5COO - The existence of Cl - -r-Ru@NiFe-LDH / IF, since Raman spectroscopy cannot retrieve the vibration of Cl, there is no corresponding peak in its spectrum; for acac-r-Ru@NiFe-LDH / IF, at 1700cm -1 The peak of CO can be retrieved, which is attributed to the presence of acetylacetonate ion.

[0058] The materials prepared in Examples 1-5 were subjected to HER electrochemical performance tests, and the test method was as follows: the materials were cut into a size of 0.25 cm × 0.25 cm, and then fixed on a platinum electrode clip as a working electrode, reversible hydrogen (RHE) as a reference electrode, a graphite rod as a counter electrode, and a nitrogen-saturated 1M KOH + 0.5M NaCl electrolyte to form a three-electrode system electrolytic cell. The catalyst was first activated by cyclic voltammetry (CV) with a scanning potential window of 0.05 to -0.5 V (vs. RHE) and a scanning rate of 0.1 V / s; then the linear sweep voltammetry (LSV) method was used to record the potential-current curve at a scanning rate of 5 mV / s.

[0059] Test results such as Figure 7 As shown by Figure 7 It is known that SO4 2- -r-Ru@NiFe-LDH has the best HER performance at 500mAcm -2 The overpotential at high current density is only 210 mV, which is better than the performance of most current seawater electrolysis HER catalysts.

[0060] The materials prepared in Examples 1-5 were subjected to an electrochemical performance test of OER, and the test method was as follows: the materials were cut into a size of 0.25 cm × 0.25 cm, and then fixed on a platinum electrode clip as a working electrode, RHE as a reference electrode, a graphite rod as a counter electrode, and an oxygen-saturated 1M KOH + 0.5M NaCl electrolyte to form a three-electrode system electrolytic cell. The catalyst was first activated by the CV method, with a scanning potential window of 1.2 to 1.8 V (vs. RHE) and a scanning rate of 0.1 V / s; then the potential-current curve was recorded using the LSV method at a scanning rate of 5 mV / s.

[0061] Test results such as Figure 8 As shown by Figure 8 It is known that SO4 2- -r-Ru@NiFe-LDH has the best OER performance at 500 mA cm -2 The overpotential at high current density is 350mV.

[0062] The material prepared in Example 1 was used as the anode and cathode for the full hydrolysis test. The test method was as follows: the material was cut into two small samples of 0.25 cm × 0.25 cm, and then they were fixed on two platinum electrode clips and placed in an H-type electrolytic cell to perform the LSV method at a scanning rate of 5 mV / s to record the potential-current curve. The test results are shown in Fig. 9 As shown by Fig. 9 It is known that SO4 2- -r-Ru@NiFe-LDH has good overall hydrolysis performance at 100 mA cm-2 The potential at the current density is 1.57 V, even at 500 mA cm -2 At a high current density, the potential is 1.72V, showing the material's superior full hydrolysis performance.

[0063] The material prepared in Example 1 was tested for HER and OER stability. The test method was as follows: the material was cut into a size of 0.25 cm × 0.25 cm, and then fixed on a platinum electrode clip as a working electrode, RHE as a reference electrode, a graphite rod as a counter electrode, and a 1M KOH + 0.5M NaCl electrolyte to form a three-electrode system electrolytic cell. The catalyst was first activated by the CV method with a scan rate of 0.1 V / s; then the current density was set to 500 mA cm by the chronopotentiometry. -2 The potential applied at the time is recorded and the time-potential curve is recorded. The test results are as follows Fig.10 As shown, the potential retention rate of HER after 160 h is 89%, and the potential retention rate of OER is 95%, indicating the superior stability and good chlorine resistance of the in-situ constructed self-supporting foam iron catalyst.

[0064] In summary, the present invention aims at the existing electrolysis of seawater catalysts, which are mostly used in small current density (≤200mAcm -2 ), it cannot be industrially applied, is expensive, and the powder catalyst needs to use a large amount of binder to coat the electrode surface, which makes the catalyst easy to fall off. This paper provides a bifunctional seawater electrolysis catalyst in situ constructed on foamed iron for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Using foamed iron as a catalyst substrate can not only provide a rich 3D porous structure to increase the specific surface area, but also release iron ions, avoid further addition of iron salts, and promote the formation of double metal hydroxides. Using hydrothermal and in-situ construction methods, the prepared material has a high degree of crystallization and an increased number of active sites, which can be used for seawater electrolysis for hydrogen and oxygen evolution at high current density. The prepared NiFe-LDH with trace ruthenium doping and different anion intercalation types has two control modes: element doping and lattice strain, which synergistically improve the activity, chlorine resistance and stability of the catalyst.

[0065] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an anion intercalated r-Ru@NiFe-LDH / IF catalyst, characterized in that: The following steps are involved: S1. Put the cleaned foamed iron into an alkaline aqueous solution of nickel salt for hydrothermal reaction to obtain a NiFe-LDH precursor with an anion intercalation layer grown on the foamed iron; S2. The anion-intercalated NiFe-LDH precursor is placed in a ruthenium chloride solution for a hydrothermal reaction again, and then taken out and dried, and the ruthenium oxide is reduced to obtain an anion-intercalated ruthenium-loaded NiFe-LDH catalyst grown on the foamed iron.

2. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 1, characterized in that: In step S1, the nickel salt is one or more of a mixture of nickel chloride hexahydrate and terephthalic acid, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel acetylacetonate; And / or, the alkalinity of the alkaline aqueous solution is regulated by one or more of urea, hexamethylenetetramine, ammonia water, sodium hydroxide, and potassium hydroxide, preferably urea.

3. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 2, characterized in that: The molar ratio of the nickel salt to urea is (1-3):5; the molar ratio of terephthalic acid to nickel chloride hexahydrate is (0.1-0.3):

2.

4. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 1, characterized in that: In steps S1 and S2, the temperature of the hydrothermal reaction is 100-150° C., and the reaction time is 10-15 hours.

5. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 1, characterized in that: In step S2, the concentration of the ruthenium chloride solution is 10-14 mmol / L, and the molar ratio of the nickel salt to ruthenium chloride is 1-3:0.2-0.

28.

6. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 1, characterized in that: In step S2, the reduction treatment is performed by thermal reduction in a mixed atmosphere of Ar and H2; The volume ratio of Ar to H2 is 1:(8-12), and the flow rate is 80-120 mL / min; the thermal reduction is performed by heat treatment at 90-110°C at a heating rate of 8-10°C / min for 1-3 hours.

7. The method for preparing the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 1, characterized in that: In step S1, the foamed iron is ultrasonically cleaned with anhydrous ethanol, 2-4 mol / L hydrochloric acid, and deionized water in sequence for 5-15 min.

8. An anion intercalated r-Ru@NiFe-LDH / IF catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. An application of the anion intercalated r-Ru@NiFe-LDH / IF catalyst according to claim 8, characterized in that: The anion intercalated r-Ru@NiFe-LDH / IF catalyst is used for electrolysis of water to produce hydrogen or oxygen.

10. The use according to claim 9, characterized in that: The water is seawater or simulated seawater, and the simulated seawater contains 1 mol / L KOH and 0.5 mol / L NaCl.

Citation Information

Cited By

  • Silver-loaded and anion-interspersed layered catalyst as well as preparation method and application thereof

    CN121853012A